Students’ Foreign Language Anxiety and English Reading Comprehension: A Correlational Study at Junior High School - Putri Nurasiah; Dedy Wahyudi (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2022)
ABSTRACTThe primary objective of this study was to examine the correlation between students’ foreign language anxiety and English reading comprehension. This study was a correlation research design. The sample was Junior High School students at the ninth grade of Junior High School 04 Dayun. Due to the small number of population in this study, which was 39 students, total sampling was taken. The study used a questionnaire to assess students’ foreign language anxiety and a test to find out students’ reading comprehension in collecting the data. To examine the relationship between two variables, this study employed the Pearson Product-Moment Correlation coefficient through SPSS 23.0. From the analysis, the result indicated that sig. (2-tailed) value was 0.001. It showed that Ho is rejected and Ha is accepted. The correlation coefficient (r) value was -0.762. It reveals that there is significant correlation between students’ foreign language anxiety and reading comprehension. To conclude, the students’ foreign language anxiety leads to reading comprehension, which means higher foreign language anxiety results in lower comprehension in reading and vice versa.